Mesh inlay, mesh kit or native tissue repair for women having repeat anterior or posterior prolapse surgery: randomised controlled trial (PROSPECT). (6th April 2020) - Glazener, CMA; Breeman, S; Elders, A; Hemming, C; Cooper, KG; Freeman, RM; Smith, ARB; Hagen, S; Montgomery, I; Kilonzo, M; Boyers, D; McDonald, A; et al.
Abstract : Objective: To compare standard (native tissue) repair with synthetic mesh inlays or mesh kits. Design: Randomised controlled trial. Setting: Thirty‐three UK hospitals. Population: Women having surgery for recurrent prolapse. Methods: Women recruited using remote randomisation. Main outcome measures: Prolapse symptoms, condition‐specific quality‐of‐life and serious adverse effects. Results: A Mean Pelvic Organ Prolapse Symptom Score at 1 year was similar for each comparison (standard 6.6 versus mesh inlay 6.1, mean difference [MD] −0.41, 95% CI −2.92 to 2.11: standard 6.6 versus mesh kit 5.9, MD −1.21, 95% CI −4.13 to 1.72) but the confidence intervals did not exclude a minimally important clinical difference. There was no evidence of difference in any other outcome measure at 1 or 2 years. Serious adverse events, excluding mesh exposure, were similar at 1 year (standard 7/55 [13%] versus mesh inlay 5/52 [10%], risk ratio [RR] 1.05 [0.66–1.68]: standard 3/25 [12%] versus mesh kit 3/46 [7%], RR 0.49 [0.11–2.16]). Cumulative mesh exposure rates over 2 years were 7/52 (13%) in the mesh inlay arm, of whom four women required surgical revision; and 4/46 in the mesh kit arm (9%), of whom two required surgical revision. Conclusions: We did not find evidence of a difference in terms of prolapse symptoms from the use of mesh inlays or mesh kits in women undergoing repeat prolapse surgery. Although the sample size was too small to be conclusive, the results provide a substantive contribution to future meta‐analysis. Tweetable abstract: There is not enough evidence to support use of synthetic mesh inlay or mesh kits for repeat prolapse surgery. Tweetable abstract: There is not enough evidence to support use of synthetic mesh inlay or mesh kits for repeat prolapse surgery.